Efficacy of semantic feature analysis as a treatment for word retrieval deficits in individuals with Broca’s aphasia - Revathi Magesh; Gauri Shankar Patil (Journal of All India Institute of Speech and Hearing, 2013)
The present study addressed efficacy of Semantic Feature Analysis (SFA) as a treatment technique for word retrieval deficits in Telugu speaking individuals with Broca’s aphasia, and to assess the generalization of trained items to untrained across the same and different semantic categories. Three Telugu speaking individuals with Broca’s aphasia participated in the study. A discrete trial treatment design was used to examine both acquisition and generalization effects of treatment. The SFA protocol using treatment pictures (animal category) was administered for 6 weeks. Naming skills were tested with untrained items within the same semantic category every 2nd week. At the end of sixth week, both trained and untrained animals names were probed. The probes for animals list continued for the next 3 weeks. At the end of 9th week, naming skills for birds and vehicles were tested and the WAB test was readministered. Maintenance effects were assessed at the end of 12 and 18 weeks. The results of WAB before and after use of the SFA protocol, baseline naming scores, scores obtained at the end of 2nd week, 4th week, 6th week, 9th week, 12th week and 18th week were tabulated and analyzed. A <0.05 of significant difference was observed for WAB scores before and after therapy indicating an objective evidence for the efficacy of SFA as a treatment option. To establish the difference in naming skills after the use of SFA, the naming subtest scores were subjected to paired samples t-test. Mean scores in the naming subtest of WAB pre & post therapy were 3.1 & 6.2 respectively. The present study suggests SFA strengthens association between target word and its prototypical semantic characteristics thereby facilitating word retrieval.